Social Construction of Female Smokers Among College Students - Mochammad Dimas Putra Setyafudin; Ahmad Ridwan; Sugeng Harianto (Jurnal Partisipatoris, 2026)
This study aims to analyze how patriarchal norms shape social stigma against female smokers among university students, given the significantly higher smoking prevalence among men in Indonesia compared to women. Gender norms influenced by this patriarchal system create a double standard that negatively stigmatizes women, such as "naughty," "cheap," and "wild." Using a qualitative approach, this study involved thirteen college students who were consciously confronting this stigma. The findings indicate that smoking is used as a symbol of resistance against gender roles that limit women's autonomy and freedom. Actors manage a "Spoiled Identity" by disguising their activities from the public sphere and using smoking as a coping mechanism against structural stress. This study concludes that gender-oriented stigma is counterproductive, rather than promoting smoking cessation. Ultimately, it can actually trigger strong resistance and reinforce smoking behavior in women.